The Influence of Product Quality, Price Perception, and Social Media Marketing Mediated by Purchase Intention on the Purchase Decisions of Samsung Smartphones Among Millennials in Sukabumi City - Iriandy, Wahyu; Hannan, Sufrin; Farradia, Yuary (Dinasti Publisher, 2024)
This study investigates the influence of product quality, price perception, and social media marketing on millennials' purchase decisions of Samsung smartphones in Sukabumi City, with purchase intention serving as a mediating variable. The research employs a quantitative approach using convenience sampling, targeting 400 respondents within the millennial age range who are Samsung users. The analysis utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that product quality and price perception significantly impact purchase decisions and intentions, while social media marketing directly affects purchase intention but not purchase decisions. Mediated by purchase intention, product quality, price perception, and social media marketing all positively influence purchase decisions. The study underscores the critical role of product quality and pricing strategies in consumer decision-making, particularly within the competitive smartphone market.